Fuzzy system in a ferrous sulfate pre-treatment of elephant grass - Godinho, Emmanuel Zullo [UNESP]; Caneppele, Fernando de Lima (FapUNIFESP (SciELO), 2022)
Renewable energies have been occupying more and more space in energy matrices worldwide, and lignocellulosic biomasses are promising for these energy sources. This study aimed to develop a fuzzy model to optimize the ferrous sulfate concentration and temperature in the pre-treatment of elephant grass. Five concentrations (10, 15, 20, 25 and 30 mM) and three temperatures (25, 40 and 55 ºC) were used as input. The application of the fuzzy model evidenced that the best results for cellulose exposure (53.1 %) were achieved by using a ferrous sulfate concentration between 20 and 22.5 mM and temperature between 39.5 and 42.5 ºC.
Sistema fuzzy em pré-tratamento de capim-elefante com sulfato ferroso
Keywords: Cellulose; Mathematical modeling; Pennisetum purpureum Schum